PEMANFAATAN SAMPAH KERTAS MENJADI PAPAN PARTIKEL SEBAGAI DINDING DEKORATIF RUANGAN - Artayani, Meldawati; Jumawan, Faris; TS, Ayu Tri (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
The problem of garbage in this discussion is devoted to the dry waste, for example waste paper. The amount of paper waste in the city of Makassar could reach 322.16 m³ / day and will continue to increase in tandem with the increasing population. As researchers attempt to reduce and increase the use of waste paper grades in particular so as to provide benefits to society in general, that is by recycling waste paper into particle board as a decorative wall of the room that is easy, cheap and environmentally friendly. The research will be conducted experiments in the laboratory and will last for 5 (five) months to determine the basic characteristics of particle board decorative paper as the wall of the room. The stages of the process, namely pegumpulan materials, materials processing as well as physical and mechanical testing. Variation of particle board that investigated the range of differences in surface texture and thickness.